Innovative Pathways for Digital-Intelligent Technology Empowerment in Law Practice Education: A Case Study of the Court Debate Course - Mao, Chunxiao (Journal of Research in Vocational Education, 2025)
This study examines the integration of digital-intelligent technology in law education through the Court Debate course, drawing on constructivist learning theory and embodied cognition theory. It elucidates the deep coupling mechanism between digital-intelligent technology and practical legal pedagogy, proposing a core logic that enhances educational effectiveness through blended reality scenario reconstruction, dynamic resource intelligent adaptation, and multimodal interaction mechanisms. Addressing three fundamental challenges in traditional practical law education—spatial fragmentation of teaching scenarios, superficial technological implementation, and singular experiential evaluation frameworks—the research presents a systematic solution featuring technology-driven approaches, intelligent empowerment, and coordinated multi-dimensional assessment. The methodology includes developing immersive cross-domain collaborative environments through virtual courtroom simulations, dynamically aligning legal theory with practical knowledge via artificial intelligence, and establishing a tripartite quantitative evaluation model based on multimodal data. The study further constructs a safeguarding framework addressing technological iteration, interdisciplinary faculty development, and technological ethics training to preserve the humanistic values of law education. The findings indicate that digital-intelligent technology effectively bridges the gap between “knowledge” and “practice” in law education through paradigm shifts in immersive contextual learning, dynamic process management, and collaborative subject engagement. This provides innovative pathways for legal professional competency development, facilitating the digital transformation of law education.